2021
DOI: 10.1038/s41467-021-21800-5
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous aldehyde accumulation generates genotoxicity and exhaled biomarkers in esophageal adenocarcinoma

Abstract: Volatile aldehydes are enriched in esophageal adenocarcinoma (EAC) patients’ breath and could improve early diagnosis, however the mechanisms of their production are unknown. Here, we show that weak aldehyde detoxification characterizes EAC, which is sufficient to cause endogenous aldehyde accumulation in vitro. Two aldehyde groups are significantly enriched in EAC biopsies and adjacent tissue: (i) short-chain alkanals, and (ii) medium-chain alkanals, including decanal. The short-chain alkanals form DNA-adduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 50 publications
2
22
0
Order By: Relevance
“… 26 We have found that ALDHs are variably affected in BE and EAC patients compared to NE (protein: Figure S4L–Q , transcript: Figure S5 J–M ). Consistent with a recent study, 10 ALDH4A1 and ALDH9A1 proteins were down‐regulated in BE and EAC relative to NE, yet ALDH1A1, ALDH1B1, ALDH16A1 were elevated (Figures S4 and S5 ). ALDH3A1 appeared to have a transient decrease in BE (Figure S4 ), before a return to healthy levels in EAC, and a previous study confirmed a decrease in ALDH3A1 in EAC by immunostaining, 10 suggesting that these changes may not necessarily be linear throughout disease stages, and changes are protein‐specific.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“… 26 We have found that ALDHs are variably affected in BE and EAC patients compared to NE (protein: Figure S4L–Q , transcript: Figure S5 J–M ). Consistent with a recent study, 10 ALDH4A1 and ALDH9A1 proteins were down‐regulated in BE and EAC relative to NE, yet ALDH1A1, ALDH1B1, ALDH16A1 were elevated (Figures S4 and S5 ). ALDH3A1 appeared to have a transient decrease in BE (Figure S4 ), before a return to healthy levels in EAC, and a previous study confirmed a decrease in ALDH3A1 in EAC by immunostaining, 10 suggesting that these changes may not necessarily be linear throughout disease stages, and changes are protein‐specific.…”
Section: Resultssupporting
confidence: 91%
“…Genotoxic aldehydes 10 and exhaled aldehydes are increased in EAC patients, 10 likely as a result of peroxidation of the elevated polyunsaturated fatty acids and reduced aldehyde detoxification. ALDHs, including ALDH1A1, ALDH1B1, ALDH2, and ALDH6A1, as well as glutathione S‐transferases, convert genotoxic aldehydes to acetyl‐CoA 40 : this can feed into the TCA cycle 41 or the ketogenic pathway, 42 both of which are upregulated in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, reduced ALDH3A2 expression, which is associated with TP53 depletion, has been demonstrated to cause reduced detoxification and endogenous accumulation of aldehyde. 37 However, changes in lipidomics profiles and regulator enzymes could occur in multiple cancers. This supports the mentioned speculations that most VOCs could correspond to broad spectrum cancers.…”
Section: Discussionmentioning
confidence: 99%
“…In acute myeloid leukemia, ALDH3A2 has been implicated to protect against fatty aldehydes generated by ferroptosis 102 . In non-hematological malignancies, reduced expression of ALDH3A2 along with several other ALDH family members has also been observed in human oesophageal adenocarcinomas; this correlated with accumulation of medium-chain aldehydes including nonanal (C9), and decanal (C10), increased markers of DNA damage, and worse overall survival 103 .…”
Section: Subheading: Fatty Aldehydesmentioning
confidence: 95%